A importância da leitura literária para alunos da EJA, do centro de recuperação de Abaetetuba-PA - RODRIGUES, Ana Célia de Almeida (2019)
The present work seeks to highlight the importance of literary reading in the recovery center of Abaetetuba-Pa, with the purpose of verifying the role of literature as an element of humanization through literary works. In this work is the work used Is this a man? From Primo Levi. Thus, regular visits were made to the classrooms of the EJA in the aforementioned recovery center, conversations directed at the classes, expositions about literature, followed by applications of questionnaires to the retrievers with questions related to reading, Literature and the work of Primo Levi Is this a man ?, who had their responses recorded and analyzed in order to apprehend the multidimensional character of the phenomena in their natural manifestation, as well as to capture the different meanings of their lived experiences. In principle, a bibliographical review was carried out of the main authors who are related to the theme, especially Antonio Candido, Michel Foucault and Primo Levi. Thus, through this work it was possible to verify the relevance of Literature to the recoverers of the center of Abaetetuba-Pa and the concrete implications in their lives.